The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-52166-w
|View full text |Cite
|
Sign up to set email alerts
|

Caffeoyl-β-d-glucopyranoside and 1,3-dihydroxy-2-tetracosanoylamino-4-(E)-nonadecene isolated from Ranunculus muricatus exhibit antioxidant activity

Abstract: This study evaluates the antioxidant activity of Ranunculus muricatus and isolation and structure elucidation of the active constituents. The aerial parts of the plants were shade dried at room temperature and powdered and extracted with methanol. The free radical scavenging activity was evaluated by 1,1-diphenyl-2-picryl-hydrazyl (DPPH) assay. The percentage scavenging activity was determined based on the percentage of DPPH radical scavenged. Column chromatography was used in order to isolate the active compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…7,8 The antioxidant activity of R. muricatus may be related to phenolic compounds such as avonoids, avonoid glycosides, and lactones found in the plant. 7,9,10 Muriolide (MO, Fig. 1) is a natural lactone that has been isolated from Ranunculus muricatus.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The antioxidant activity of R. muricatus may be related to phenolic compounds such as avonoids, avonoid glycosides, and lactones found in the plant. 7,9,10 Muriolide (MO, Fig. 1) is a natural lactone that has been isolated from Ranunculus muricatus.…”
Section: Introductionmentioning
confidence: 99%
“…Ranunculus has a total of 600 species that have been reported to exhibit various medical effects. For example, Ranunculus muricatus L. has been used as a folk remedy for treating heart disease, cancer, and dental diseases [14][15][16]. Ranunculus arvensis L. has been utilized to cure arthritis, asthma, hay fever, rheumatism, psoriasis, and gut disease [17].…”
Section: Introductionmentioning
confidence: 99%
“…Ranunculus arvensis L. has been utilized to cure arthritis, asthma, hay fever, rheumatism, psoriasis, and gut disease [17]. In addition, Ranunculus muricatus L. and Ranunculus arvensis L. methanol extracts were found to contain potent antioxidants [14,17,18]. In addition, it has been reported that methanol extracts of Ranunculus peltatus subs were effective against contact dermatitis [19], and Ranunculus constantinopolitanus has anti-inflammatory activities [20].…”
Section: Introductionmentioning
confidence: 99%
“…R. muricatus is used in traditional medicine to treat cough, asthma [ 10 ], dysentery, jaundice, diarrhea, eczema, urinary infections, leprosy, and ringworm infection [ 11 , 12 ]. R. muricatus has also been employed in folk medicine to treat cancer, heart diseases, and dental diseases [ 13 , 14 , 15 ], and R. muricatus extracts have been reported to possess antioxidant [ 16 ], antifungal, antibacterial, and cytotoxic effects [ 17 ]. R. muricatus is furthermore employed to treat tonsillitis diseases in traditional medicine protocols in India [ 18 ].…”
Section: Introductionmentioning
confidence: 99%